X-Ray Computed Tomography Analysis of Sajau Coal, Berau Basin, Indonesia: 3D Imaging of Cleat and Microcleat Characteristics. (5th July 2015) - Hamdani, Ahmad Helman
Abstract : The Pliocene Sajau coals of the Berau Basin area have a moderately to highly developed cleat system. Mostly the cleat fractures are well developed in both bright and dull bands, and these cleats are generally inclined or perpendicular to the bedding planes of the seam. The presence of cleat networks/fractures in coal seam is the important point in coalbed methane prospect. The 3D X-ray computed tomography (CT) technique was performed to identify cleats characteristics in the Sajau coal seams, such as the direction of coal cleats, geometry of cleat, and cleats mineralization. By CT scan imaging technique two different types of natural fractures observed in Sajau coals have been identified, that is, face cleats and butt cleats. This technique also identified the direction of face cleats and butt cleats as shown in the resulting 3D images. Based on the images, face cleats show a NNE-SSW direction while butt cleats have a NW-SE direction. The crosscutting relationship indicated that NNE-SSW cleats were formed earlier than NW-SE cleats. The procedure also identified the types of minerals that filled the cleats apertures. Based on their density, the minerals are categorized as follows: very high density minerals (pyrite), high density minerals (anastase), and low density minerals (kaolinite, calcite) were identified filling the cleats aperture.